PENGARUH LIKUIDITAS, SOLVABILITAS DAN AKTIVITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR PROPERTY DAN REAL ESTATE DI BURSA EFEK INDONESIA - Dasriyan Saputra; Syanti Dewi Harahap; Andi Juhairah (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This research aims to determine the effect of liquidity (Current Ratio), solvency (Debt to Equity Ratio), and activity (Total Asset Turnover) on profitability (Return on Asset). This research is quantitative in nature. The population on this study are property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) for 2020-2024 period. The sampling technique used was purposive sampling. The research sample includes 6 companies out of total population of 37 companies. The data analysis technique used is multiple linear regression assisted by SPSS 25 program. The results of the t-test show that partially, the liquidity variable (Current Ratio) has a positive and significant effect on profitability (Return on Asset), the solvency variable (Debt to Equity Ratio) has a negative and significant effect on profitability (Return on Asset), and activity variable has a negative and significant effect on profitability (Returnq on Asset). Meanwhile, the results of the F-test show that simultaneously, liquidity (Current Ratio), solvency (Debt to Equity Ratio), and activity (Total Asset Turnover) have a significant effect on profitability (Return on Asset).